The implementation of fundamental harmonic approximation technique on electric vehicle wireless charger - Pairindra, Worapong; Khemmook, Panya; Khomfoi, Surin (My University, 2021)
This paper presents the electric vehicle (EV) wireless charger by using the practical design frequency converter. A 500 W LLC series resonant full-bridge converter for demonstrating prototype with the standard charging frequency range 85 kHz to 100 kHz is connected to the transmission coils with 10 cm air gap and performed a power transfer from the source to the EV batteries. The resonant converter with the Fundamental Harmonic Approximation (FHA) technique is chosen in this proposed paper for transferring the highly magnetic coupling between the transmitter side to the pickup side. The overall system is designed by MATLAB/Simulink program, and the experimental result efficiency can be measured out by approximately 80%.
Keywords: Electric vehicle; Fundamental Harmonic Approximation; Resonant Converter; Wireless charger